“Scientist” Through The Eyes of Primary School Teacher Candidates - Arslan, Ayten; Kartal, Ayça (Fırat University, 2021)
The aim of this research is to examine the images of elementary teacher candidates for the concept of “scientist”, which is one of the most important components of the nature of science, in terms of various variables. The study group of the research consists of the elementary teacher candidates studying at the faculty of education. In this research, phenomenology pattern was used. The data were collected between May and December 2019. In the results obtained, it is seen that the first thing that comes to mind in the perceptions of scientist gender of all elementary teacher teachers is “male”. They stated that the results of what the elementary teacher candidates would like to study and if they were a scientist were examined. They stated that they mostly wanted to study science. They stated that they wanted to work on subjects such as space, universe, astronomy and time travel in science.

Bu araştırmanın amacı, bilimin doğasının en önemli bileşenlerinden biri olan “bilimci” kavramına yönelik sınıf öğretmeni adaylarının imajlarını çeşitli değişkenler açısından incelemektir. Araştırmanın çalışma grubunu eğitim fakültesi sınıf öğretmenliği anabilim dalında öğrenim gören öğretmen adayları oluşturmaktadır. Bu araştırmada, nitel araştırmalardan fenomenoloji deseni kullanılmıştır. Veriler 2019 yılı Mayıs-Aralık ayları arasında toplanmıştır. Araştırmandan elde edilen sonuçlara göre tüm sınıf öğretmeni adaylarının bilimci cinsiyeti algılarında akla ilk gelenin “erkek” olduğu tespit edilmiştir. Öğretmen adayları çoğunlukla fen bilimleri üzerine çalışmalar yapmak istediklerini belirtmişlerdir. Fen bilimleri içerisinde özellikle uzay, evren, astronomi, zamanda yolculuk gibi konular üzerine çalışmak istediklerini belirtmişlerdir.
SINIF ÖĞRETMENİ ADAYLARININ GÖZÜNDEN “BİLİMCİ”